2006
DOI: 10.1111/j.1365-2265.2006.02666.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating adiponectin in type 1 diabetes is associated with long diabetes duration

Abstract: The increase in circulating adiponectin concentrations in patients with type 1 diabetes appears to be strongly associated with long diabetes duration, irrespective of the metabolic control. Among other factors, a putative role for residual beta-cell function in the regulation of circulating adiponectin levels can be considered but we did not find sufficient evidence for this in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
3
29
3
Order By: Relevance
“…Similar results have been reported in the literature in type I DM [5][6][7][8][9], whereas type II DM has been associated with low serum adiponectin levels [10][11][12][13]. The increase in serum adiponectin levels in type I DM, in contrast to type II DM, may be due to a lack of insulin; glucose and insulin may play an important role in the increased serum adiponectin levels observed in type I DM [5,14] However, Berg et al showed that serum adiponectin levels do not change in mice after the onset of diabetes although the insulin levels decrease dramatically [15].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results have been reported in the literature in type I DM [5][6][7][8][9], whereas type II DM has been associated with low serum adiponectin levels [10][11][12][13]. The increase in serum adiponectin levels in type I DM, in contrast to type II DM, may be due to a lack of insulin; glucose and insulin may play an important role in the increased serum adiponectin levels observed in type I DM [5,14] However, Berg et al showed that serum adiponectin levels do not change in mice after the onset of diabetes although the insulin levels decrease dramatically [15].…”
Section: Discussionsupporting
confidence: 80%
“…Studies on DM duration have also not found a relationship between the type I DM duration and serum adiponectin levels [5,16]. However, Lindstrom found that the serum adiponectin levels were increased in patients with a diagnosis of type 1 DM for more than 10 years and stated that this may be due to the disturbed kidney functions related to the duration of DM [8]. Studies have also not found a relationship between metabolic control and the adiponectin levels [19].…”
Section: Discussionmentioning
confidence: 89%
“…Similar results have been obtained with respect to microangiopathy (19,42) and long diabetes duration (43). Unlike C-reactive protein, adiponectin is considered to be inversely related to obesity and dyslipidemia, and low levels have been linked to cardiovascular disease (44,45).…”
Section: Discussionsupporting
confidence: 78%
“…Our results may provide an explanation for the discrepancy showing that although clinical and animal studies all indicated that APN is cardioprotective, those with type 1 diabetes are more susceptible to myocardial IR and not sensitive to IPo irrespective of increased or decreased APN seen in patients and animals with type 1 diabetes (42,43). Our results showed that loss of the APN cardioprotective effect seen in the late stage of diabetes is largely due to the malfunction of APN, especially the impaired AdipoR1/Cav3 signaling, but not merely the reduction of APN content.…”
Section: Discussioncontrasting
confidence: 41%